Can GoTo survive? Assessing financial performance and bankruptcy risks post-divesting Tokopedia - Ramadhan, Rico Putra; Wahyuningsih, Sulistya Dewi (Institute of Computer Science (IOCS), 2025)
This study examines the initial impact of Tokopedia's divestment following the acquisition of TikTok on PT GoTo's financial performance and bankruptcy risk. As Tokopedia is the second-largest revenue contributor to GoTo, this strategy has the potential to affect the company's financial condition. With a focus on financial performance and the risk of corporate bankruptcy, the research combines quantitative methods with case studies. The indicators used in this study include financial performance (ROA, ROE, NPM, QR, DAR, DER, TATO) and bankruptcy risk analyzed using the Grover model. Data was obtained from GoTo's annual financial statements for the period from 2022 to 2024. The results showed that GoTo's divestment of Tokopedia had a positive initial impact in terms of profitability and cost efficiency. This is evidenced by all the proposed indicators showing better results after GoTo divested Tokopedia. The Grover model also shows the transition of GoTo from the distress zone to the safe zone. These results are driven by the consolidation of the core business (Gojek & GoPay) as well as the support of government regulations and the improvement of post-COVID-19 on-demand conditions. The implications of this study provide insight for stakeholders regarding GoTo's financial resilience after the Tokopedia divestment and provide an early indication of financial risk mitigation for the future.